Parents and Peers: Parental Neighbourhood- and School-Level Variation in Individual Neighbourhood Outcomes over Time - Elise de Vuijst; Maarten van Ham (Institute of Labor Economics (IZA), 2017)
There is a link between the socio-economic outcomes of parents and their children over the life course. Intergenerational transmissions were repeatedly shown for socioeconomic characteristics and (dis)advantage, but recently also for residential neighbourhood status. Previous research from the Netherlands, Sweden, and the US shows that children from disadvantaged parental neighbourhoods experience long-term exposure to similar neighbourhoods as adults. However, there are multiple parallel socio-spatial contexts besides the residential space to which individuals are exposed on a daily basis, such as households, schools, and places of work and leisure, which may also influence their outcomes. For children and adolescents, the school environment may be especially important. This study contributes to the literature by examining the joint influence of the parental background, the parental neighbourhood, and a compositional measure of the school environment, on the neighbourhood trajectories of Dutch adolescents after leaving the parental home. We use longitudinal register data from the Netherlands to study a complete cohort of school-going home-leavers, who were followed from 1999 to 2012. We fit cross-classified multilevel models, in order to split up the variance components of schools and parental residential neighbourhoods over time. We find that poverty concentration in the parental neighbourhood plays an important role in determining their children's residential outcomes later in life. Some variation in individual neighbourhood outcomes at the level of the secondary school remains unexplained.
Keywords: I30; J60; P46; R23; 330; intergenerational neighbourhood effects; secondary school; peer effects; contextual effects; register data